Surface instability of metal anode in all-solid-state batteries. (15th October 2022) - Gao, Tianhan; Lu, Wei
Highlights: A model couples electrochemistry, stress and defects in a solid-state electrolyte. A moving mesh approach is used to capture the anode surface growth. Simulations reveal how defects and deformation mode affect deposition instability. Various factors work together to trigger nanoscale surface instability. Abstract: The all-solid-state battery with metal anode is gaining increasing attention due to its high energy density. However, material inhomogeneity in the solid-state electrolyte can trigger an anode surface to lose its stability during electrodeposition, leading to nucleation of nanoscale dendrites. In this paper, a model that couples electrochemistry and mechanical stress is developed and implemented into finite element simulations based on the moving mesh method. By precisely defining the location of an interface and the interfacial properties with moving mesh, we capture the mechanism of how an anode losses surface stability near defect regions from a nanoscale perspective. The effects of applied current density, ion diffusivity, geometrical parameters of the defect region, Young's modulus of the solid-state electrolyte and of the defect region, and initial salt concentration are investigated. The results show that these factors can cause various deformation modes in the solid-state electrolyte as a result of stress field and chemical potential distribution, and significantly affect the distribution of electrodeposition current density on the anode surface. High applied current density, low ion diffusivity of the solid-state electrolyte, larger thickness and more tilting of the defect, low Young's modulus, and high initial salt concentration can all contribute to promote surface instability. This work provides a comprehensive insight into how various factors trigger a metal surface to lose its stability at nanoscale, which can guide the design of material properties of solid-state electrolyte and the operational strategies of all-solid-state batteries.